Population Instability of Tehran Metropolis vs 12 Regions in Tehran Province: a Brief Case Study - Shabazzadegan, Yasmin; Arzjani, Zahra (International Journal of Bio-resource and Stress Management, 2011)
Distribution of cities and consequently the concentration of urban population in Iran are not uniform and homogeneous. This is not only due to natural factors but is caused by the trend of civilization, evolution and changes in cities, of which the effect of the later is much more than the former. Due to structural inefficiencies in the planning system of the country and in the absence of land preparation plans, urbanism in Iran has caused a discordant urban system which has ended into unbalanced focus and concentration of population and activities in urban hierarchy. Tehran as one of the 20 large cities in the World and the largest Iranian metropolis is the most sensible instance of this phenomenon. Since the beginning of the current century, especially in recent decades, skeletal-spatial structure of this city has been the subject of vast heterogeneous and dispersed changes. On the other hand, 12 regions of Tehran province has witnessed continuous population drains, the departure of local residents and traditional families. Iranian Government needs to address such issues for balanced population growth and distribution implementing suitable policies.